Financing Higher Education in Latin America - de Fanelli, Ana Garcia (International Higher Education, 2014)
Latin American countries have been enjoying a strong growth during the 2000s for the first time since the debt crisis of the 1980s. This article focuses on some of the changes that took place during these boom years with regard to public and private funds earmarked for tertiary education, some consequences of this funding pattern in terms of equity, and the main innovations in funding mechanisms put in place to allocate public funds.